2009
DOI: 10.1055/s-0029-1185340
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Structurally Diverse Amaryllidaceae Alkaloids and their Synthetic Derivatives: Discovery of Novel Leads for Anticancer Drug Design

Abstract: Twenty nine Amaryllidaceae alkaloids and their derivatives belonging to five most common groups, including lycorine-, lycorenine-, tazettine-, crinine-, and narciclasine-types, were evaluated for antiproliferative, apoptosis inducing and antiinvasive activities in vitro. The antiproliferative properties of each test compound are in agreement with those reported in the literature, while the high potency of amarbellisine is reported for the first time. It was also found that with the exception of ungeremine, ama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 52 publications
(61 reference statements)
2
122
0
Order By: Relevance
“…This derivative may also be a prodrug of 1 and its somewhat weaker apoptosis inducing potential in Jurkat cells (Fig. 8) may be explained by the 24 h treatment, which may be insufficient for the complete hydrolytic removal of the acetate ester (Evidente et al 2009). …”
Section: Pretazettine Tazettinementioning
confidence: 96%
See 2 more Smart Citations
“…This derivative may also be a prodrug of 1 and its somewhat weaker apoptosis inducing potential in Jurkat cells (Fig. 8) may be explained by the 24 h treatment, which may be insufficient for the complete hydrolytic removal of the acetate ester (Evidente et al 2009). …”
Section: Pretazettine Tazettinementioning
confidence: 96%
“…The collagen invasion assay revealed potent antiinvasive properties associated with N-methyllycorine iodide (6), hippeastrine (13), clivimine (17), buphanamine (23), and narciclasine tetraacetate (26), all of which were tested at non-toxic concentrations. These results could represent a starting point to carry out a structure-activity relationship study of alkaloids, synthetic derivatives and natural analogues for each ring-type group with the aim to find compounds with significantly increased antiinvasive activity (Evidente et al 2009). …”
Section: Antiinvasive Activitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Homoharringtonine is a marketed drug for the treatment of chronic myeloid leukaemia 37 . Lycorine and narciclasine are alkaloids known for their medicinal and toxic properties 38 . T-2 toxin, deoxynivalenol and verrucarin A are widespread mycotoxins representatives of the three major trichothecenes subclasses 39 .…”
Section: The 60s Trna E-sitementioning
confidence: 99%
“…The study found that Galanthamine and O-desmethyl galantamine from Galanthamine type alkaloids have anti-acetylcholinesterase(AchE) activity. Galantamine the performance of AchE inhibition is competitive reversible inhibition, the role of the IC50 is 1.9 μmol/L [27] ; 1-O-acetyllycorine of Lycorine type alkaloids has significant inhibitory activity and its intensity is equal to 2 times of Galanthamine, Lycorine of Lycoris type alkaloids, 1,2 diacetyl Lycorine anti-AchE activity is poor [28] ; In addition, the study also found that montanine of AchE showed some inhibition, the strength of galanthamine was slightly lower [29] . Narciprimine and 6-Hydroxycrinamine also has anti-AchE activity [30] .…”
Section: Anti-tumor Effectmentioning
confidence: 99%